Mental health policy, nursing education and difficulties in care practice (Research, Society and Development, 2020)
This study aims to analyze the training of nurses from public and private educational institutions in the city of São Paulo considering the changes proposed by the National Mental Health Policy and the Brazilian Psychiatric Reform. Research with a qualitative, descriptive-exploratory approach, using the methodological framework of document and content analysis. Interviews were carried out with the professors responsible for the Mental Health disciplines and the documentary analysis of the Political-Pedagogical Projects that guide the researched nursing courses was elaborated. Problems were identified that interfere with the quality of the education offered, mainly with regard to the practices of internships in substitute services, of which the disarticulation and inadequate functioning of the mental health care network stand out; the deficiency in the number of services to meet the demand of the population and schools. In addition, there are difficulties in contracting with health management to establish the fields of practice due to the outsourcing of the sector and in the association of the given theory, in the classroom, with the practices developed in the assistance units. It was noticed that educational institutions did not offer training in undergraduate nursing in line with the changes proposed by the National Mental Health Policy and the assumptions of Psychiatric Reform.